Florida's Environment - North Central Region - Martin B. Main; Ginger M. Allen (EDIS)
This 7-page fact sheet is part of the Florida's Environment series. Written by Martin B. Main and Ginger M. Allen, and published by the UF Department of Wildlife Ecology and Conservation, July 2007.